Macroprudential Policy on Banking Sector in Indonesia - Feny Putri Emyliani; Dwi Wulandari; Siti Rosnita Sakarji; Bagus Shandy Narmaditya (Faculty of Economics and Business, University of Pasundan, 2018)
This study investigates the implementation of macroprudential policy on banking sector and society. The research applied a descriptive analysis by using an in-depth interview with Bank Indonesia, representative of commercial bank, and society. The result showed that macroprudential policy has no impact on individual, but it had an impact on industrial banking specifically on bank credit lending which caused by LTV regulation. The society responses to the LTV policy is that the majority do not object to the imposition of a maximum limit for housing credit enacted by bank because of the relatively long credit period. Furthermore, another instrument of macroprudential such as GWM-LFR does not have an impact on banking sector and society but capital buffer instrument assuming a sluggish economy condition is assessed to have an impact on lending by banks.